2009
DOI: 10.1186/1471-2458-9-297
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical performance measures, bone mineral density, falls, and the risk of peripheral fracture: a cross-sectional analysis

Abstract: Background: Several factors, in addition to low bone mineral density (BMD), have been identified as risks for fractures, including reduced levels of physical activity, poor balance and low physical performance. The aim of this study was to evaluate the relationship between physical performance measures, BMD, falls, and the risk of peripheral fracture in a population sample of Moroccan women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 32 publications
1
40
0
3
Order By: Relevance
“…Notably absent are any recommendations to consider the role of balance training and physical conditioning when evaluating a patient with a fragility fracture of the forearm or elsewhere. Current practice trends mirror these guidelines, as evaluation for osteoporosis is becoming a common consideration following these injuries 32,33 , and assessment and treatment of fall risk are more often overlooked 34,35 . There were several potential limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably absent are any recommendations to consider the role of balance training and physical conditioning when evaluating a patient with a fragility fracture of the forearm or elsewhere. Current practice trends mirror these guidelines, as evaluation for osteoporosis is becoming a common consideration following these injuries 32,33 , and assessment and treatment of fall risk are more often overlooked 34,35 . There were several potential limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the physical effects of the fracture event, we chose to evaluate patients who had sustained a distal radial fracture more than 6 months prior to the start of this study and also took steps to ensure that it was an isolated wrist injury without neurologic or musculoskeletal compromise outside of the afflicted upper extremity. Unlike proximal femoral or vertebral compression fractures, which result in permanent alterations in a patient's lower-extremity function and balance, distal radial fractures offer a unique model to potentially study a patient's preexisting postural stability deficit after injury has occurred as no permanent change in postural control should occur as a result of a wrist fracture 35,36 . Additionally, psychological effects from the fracture event itself may also affect balance.…”
Section: Discussionmentioning
confidence: 99%
“…Among healthy men and women poor performance on tests of neuromuscular function (such as grip strength, the timed up and go (TUG) test, five times sit-to-stand test, and 8-feet timed walk test) are associated with falls, low BMD, and fractures [69][70][71].…”
Section: Tests Of Neuromuscular Functionmentioning
confidence: 99%
“…Besides, the results show that women with osteopenia also have increase in the trunk dislocation, and based on a study by Siris et al, 2001 which shown that osteopenic women had 1.8-fold higher rate of fracture than women with normal BMD, a careful attention should be paid to this population in order to reduce the risk of falls. A recent study evaluated the physical performance of women aged 45 to 64 years, through evaluations that included sit-to-stand test (Khazzani et al, 2009). The results showed that low physical performance was associated with low BMD of spine and hip.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that low physical performance was associated with low BMD of spine and hip. In addition, some studies shown that regular training to strengthen the muscles of the lower limbs, especially the quadriceps, are effective for increasing muscle power, static and dynamic balance, thus improving performance activities of daily living, which includes the act of sitting down and up (Khazzani et al, 2009;Teixeira et al, 2010). Also, high-impact loading exercise has shown to be efficient to increase bone mass and geometry in postmenopausal women (Hamilton et al, 2010;Iwamoto et al, 2010).…”
Section: Discussionmentioning
confidence: 99%